Pengaruh Dukungan Sosial Dosen dan Persepsi terhadap Aktivitas Membaca Mahasiswa : Kasus IAIN Kerinci dan STAI AN Andwah Kuala Tungkal, Jambi - Hendra Gunawan; Mila Wahyuni; Afriansyah Afriansyah (Universitas Indraprasta PGRI Jakarta, 2022)
This paper aims at knowing the influence of lecturer's social support and perception on students' reading activities of IAIN Kerinci and STAI An Nadwah Kuala Tungkal, Jambi. This paper applies the principles of quantitative research with a sample of 270 students from IAIN Kerinci and 170 students from STAI An Nadwah Kuala Tungkal. This samples are processed using the Slovin formula, while the questionnaire instrument uses the Likert scale as a survey instrument for variables of reading interest, perception of reading activity and lecturer's social support which is then tested for feasibility using construct validity. The research was conducted from June to October 2021. This paper concludes that lecturers' social support and perception of reading activities together affect reading interest of IAIN Kerinci students by 66.2% and 33.8% is influenced by other factors, while for STAI An Nadwah Kuala Tungkal students by 41.3% and 58.7% influenced by other factors. This social support is in the moderate category. Meanwhile, students' perceptions of reading activities showed positive and negative perceptions.